Effect of Endorphin Massage on The Level of Anxiety among >36 Weeks Pregnant Women - Liya Lugita Sari; Kintan Anissa (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
The weeks leading up to delivery are always anxiety-provoking for pregnant women. Pregnant women may have negative effects from anxiety such as prenatal attachment, the term used to describe the bonding between both mother and baby. Such condition can lead to poor uterine contraction, prolonged labor, uterine atony, bleeding wounds, infections, maternal exhaustion and shock, while also increasing the likelihood of premature birth and low birth weight. A non-pharmacological therapy named endorphin massage may stimulate the body to release endorphins. Such hormone may minimize anxiety and promote maternal and fetal well-being. This study aims to determine the effect of endorphin massage on the level of anxiety among more than 36 weeks pregnant women at Private Practice Midwife Listiorini in 2022. This was a pre-experimental study with a one group, pre-test post-test design. The current study was conducted on March 20-April 20 at Private Practice Midwife Listiorini. The accident sampling approach was applied to select the study samples, which consisted of 30 more than 36 weeks pregnant women who performed ANC visits at Private Practice Midwife Listiorini and met the inclusion criteria. The instruments used were the HARS Scale and the Endorphin Massage SOP. In accordance with the results, there was a decrease in the median anxiety levels of pregnant women after receiving the endorphin massage intervention by 8.17. The Wilcoxon statistical test result showed a p-value of 0.000 (less than 0.05), which indicated that endorphin massage intervention had an effect on the level of anxiety among pregnant women in the third trimester. The study finding is expected to help pregnant women lowering their anxiety levels before delivery.